Managing the failing renal allograft: navigating a complex topography - Kendrick, Elizabeth A. (Frontiers in Nephrology, 2025)
Recipients of kidney transplants often outlive the function of the renal allograft will need ESRD management. Patients face a higher risk of mortality in the period of transition from failing allograft to dialysis. Long term risk of cardiovascular complications and risk of infections and cancer with use of long-term immune suppression contribute to poor outcomes. Patients with failing transplants appear to have poorer control of CKD complications and are more likely to initiate hemodialysis using a catheter. Outcomes of peritoneal dialysis in the setting of the failing allograft in general are equivalent to hemodialysis. Management of these patients in transplant center clinics specifically focused on patients with failing allografts may have benefit, but maximal utility has yet to be demonstrated. Patients with failed transplants can have a survival benefit with retransplant, even in older patients. There may not be a benefit to retransplant in patients older than 70 years of age. Patients with failing renal grafts should be assessed as to whether they are potential candidates for retransplant prior to needing to start dialysis to allow for identification of a living kidney donor or to be listed as soon a possible on the kidney transplant wait list as to minimize the wait time on dialysis. Decisions regarding reduction of immunosuppression once the patient has started dialysis should be made with guidance from the transplant center in the context of patient-centric factors such as candidacy for retransplant and minimizing complications of long-term immunosuppression.